(untitled) (Terr@ Plural, 2023)
The Leptocoeliidae family (genera Anabaia, Australocoelia, Eocoelia, Leptocoelia, Leptocoelina and Pacificocoelia) has an important place in the global paleobiogeography, during the Silurian and Devonian. During these periods, global climate changes impacted a lot of invertebrate faunas in the epicontinental seas of Gondwana. In the Silurian, the genus Eocoelia reached a cosmopolitan behavior, while Leptocoelia emerged by adaptive sympatric processes and Anabaia became extinct. After that, during the Devonian, the genus Australocoelia emerged and reached cosmopolitan levels while Leptocoelina and Pacificocoelia emerged by sympatries in the equatorial regions. Australocoelia, during the Devonian, occupied the same ecological niches that were previously occupied by Anabaia in the Silurian. It can be said that the same occurred with Pacificocoelia and Eocoloelia in the seas of Laurentia, configuring a process of succession of faunas.